Mucoadhesive Amphiphilic Methacrylic Copolymer-Functionalized Poly(epsilon-caprolactone) Nanocapsules for Nose-to-Brain Delivery of Olanzapine - Fonseca, Francisco N.; Betti, Andresa H.; Carvalho, Flavia C. [UNESP]; Gremiao, Maria P. D. [UNESP]; Dimer, Frantiescoli A.; Guterres, Silvia S.; Tebaldi, Marli L.; Rates, Stela M. K.; Pohlmann, Adriana R. (Amer Scientific Publishers, 2015)
Nose-to-brain drug delivery has been proposed to overcome the low absorption of drugs in central nervous system due to the absence of brain-blood barrier in the olfactory nerve pathway. However, the presence of a mucus layer and quick clearance limit the use of this route. Herein, amphiphilic methacrylic copolymer-functionalized poly(epsilon-caprolactone) nanocapsules were proposed as a mucoadhesive system to deliver olanzapine after intranasal administration. In vitro evaluations showed that these nanocapsules were able to interact with mucin (up to 17% of increment in particle size and 30% of reduction of particle concentration) and nasal mucosa (2-fold higher force for detaching), as well as to increase the retention of olanzapine (about 40%) on the nasal mucosa after continuous wash. The olanzapine-loaded amphiphilic methacrylic copolymer-functionalized PCL nanocapsules enhanced the amount of drug in the brain of rats (1.5-fold higher compared to the drug solution). In accordance with this finding, this formulation improved the prepulse inhibition impairment induced by apomorphine, which is considered as an operational measure of pre-attentive sensorimotor gating impairment present in schizophrenia. Besides, nanoencapsulated olanzapine did not affect the nasal mucosa integrity after repeated doses. These data evidenced that the designed nanocapsules are a promising mucoadhesive system for nose-to-brain delivery of drugs.
Keywords: Nose-to-Brain Delivery; Methacrylic Copolymer; Poly(epsilon-caprolactone); Nanocapsule; Olanzapine; Schizophrenia